David Keyworth, Troublesome Corpses: Vampires and Revenants from Antiquity to the Present. - Hartney, Christopher (Journal for the academic study of religion, 2008)
David Keyworth, Troublesome Corpses: Vampires and Revenants from Antiquity to the Present. Southend-on-Sea, Desert Island Books, pp. 320, ISBN 9781905328307.